A regulatory BMI1/let‐7i/ERK3 pathway controls the motility of head and neck cancer cells. Issue 2 (12th January 2017) - Elkhadragy, Lobna; Chen, Minyi; Miller, Kennon; Yang, Muh‐Hwa; Long, Weiwen
Abstract : Extracellular signal‐regulated kinase 3 (ERK3) is an atypical mitogen‐activated protein kinase (MAPK), whose biological activity is tightly regulated by its cellular abundance. Recent studies have revealed that ERK3 is upregulated in multiple cancers and promotes cancer cell migration/invasion and drug resistance. Little is known, however, about how ERK3 expression level is upregulated in cancers. Here, we have identified the oncogenic polycomb group protein BMI1 as a positive regulator of ERK3 level in head and neck cancer cells. Mechanistically, BMI1 upregulates ERK3 expression by suppressing the tumor suppressive microRNA (miRNA) let‐7i, which directly targets ERK3 mRNA. ERK3 then acts as an important downstream mediator of BMI1 in promoting cancer cell migration. Importantly, ERK3 protein level is positively correlated with BMI1 level in head and neck tumor specimens of human patients. Taken together, our study revealed a molecular pathway consisting of BMI1, miRNA let‐7i, and ERK3, which controls the migration of head and neck cancer cells, and suggests that ERK3 kinase is a potential new therapeutic target in head and neck cancers, particularly those with BMI1 overexpression. Abstract : Extracellular signal‐regulated kinase 3 (ERK3) is an atypical MAPK, which is upregulated in multiple cancers and promotes cancer cell migration/invasion and drug resistance. However, little is known about the molecular mechanisms by which ERK3 level is upregulated in cancers. In our study, we identify a molecular pathway consisting of the oncogenic polycomb group protein BMI1, the tumor suppressor miRNA let‐7i, and ERK3, which controls the migration of head and neck cancer cells.